The important of understanding and teaching Islamic Law in Asia - Nik Mahmod, Nik Ahmad Kamal (Cambridge University Press, 2006)
This paper will deal with the need to understand Islamic Law in the context of a number of prevailing misconceptions about it. It then discusses the place and importance of Islamic Law in the LL.B. (Bachelor of Law) programmes in Malaysia and elsewhere in Asia. The focus will be on what courses are to be taught, and how they are to be taught. The paper also attempts to shed some light on the possible ways to harmonise Islamic Law with concurrent secular (or civil) law, and offers a vision of the future of Islamic legal education.